The effectiveness use of teaching aid in teaching and learning Science subject for Pre School students in SK Penghulu Imban / Rosetar Berlula Pingan - Pingan, Rosetar Berlula (2015)
The purpose of this study was to test the effectiveness of using teaching tools in the teaching and learning of science in pre-schools. Teaching and learning science process will not succeed without material realized where children explore their own learning. Therefore the use of teaching aids in the classroom is very important. Teaching aids are very important in the process of teaching and learning. The study was conducted using experimental methods, questionnaire and answer, and survey forms. Data were analyzed using methods appropriate to it. The sample consisted of 10 students in preschool at SK Penghulu Imban, Selangau. The findings of this study demonstrate the effectiveness of using teaching aid in the teaching and learning science in preschool. Perception is very encouraging students in the use of teaching aid presentations in learning. Teachers also support this method in implementing the teaching and learning process.